Radiolarians (Class Polycystina) indeep-sea sediments from the Pacific Ocean off Costa Rica - Rodríguez–Jiménez, Alexis (2024)
Introduction. Radiolarians are an important group of marine planktonic protists. The polycystines (Phylum Radiozoa, Class Polycystina) are a group of radiolarians whose skeletons are made of opal (amorphous silica) and form the basis for their taxonomic classification. There are few recent studies of radiolarians in Costa Rica. Objective. This research seeks to create the first taxonomic guide of radiolarians present in Holocene sediments (from 11 000 years ago to the present) of the Costa Rican Pacific seabed. Methods. Between late 2018 and early 2019, two oceanic expeditions: Rock Hits and Costa Rica Deep-Sea Connections, respectively, collected 13 sediment cores from the Costa Rican Pacific seabed. Using a modified methodology created for these investigation, 64 samples were obtained from which radiolarian remains were extracted for taxonomic analysis. Obtained radiolarians were mounted for taxonomic analysis using optical and scanning electron (SEM) microscopy. Results. A total of 119 species of Polycystina were identified, distributed among 15 families belonging to the orders Collodaria (one family and eight species), Spumellaria (seven families and 62 species), and Nassellaria (seven families and 49 species). Conclusion. This study identifies several taxa (119) like those reported in studies conducted near the Pacific coast of Costa Rica, but less than half of those reported from the Eastern Equatorial Pacific (EEP).